Sugarcane Extract (Polygain™) Supplementation Reduces Enteric Methane Emission in Dairy Calves - Richard Osei-Amponsah; Pragna Prathap; Frank R. Dunshea; Richard Eckard; Matthew Flavel; Muhammed Elayadeth-Meethal; Surinder S. Chauhan (Animals)
Polygain™ (PG), a polyphenolic extract from sugarcane, has recently been identified as a potential additive to reduce methane (CH4) emissions in livestock. This experiment examined the effects of PG on the enteric CH4 emission from Holstein Friesian weaned calves. Calves were allocated to annual pasture grazing and received supplementary pellets (200 g/calf/day; Barastoc calf-rearer cubes—Ridley Corporation). The experimental design followed was a completely randomized design (CRD), comprising 24 female calves (4–5 months old) allocated to two equal groups; control (standard pellets) vs. treatment (pellets formulated by adding PG to control pellets to deliver 10 g PG/calf/day). Experimental diets were fed for three months between August and November 2023, including a two-week adaptation period. Calves were weighed at the start and at the end of the study. A GreenFeed (C-Lock Pvt Ltd.) emission monitoring unit (GEM) was used to measure GHG emissions from the experimental calves in their groups in a 2-day rotational cycle. During a visit to the GEM, the calves were encouraged to enter an enclosed area or individual feeding stall where enteric CH4, CO2, O2, H2, and H2S measurements were taken. The results indicated a significant effect of PG supplementation on enteric methane emission in calves, with a lower production of CH4 in calves supplemented with PG (26.66 ± 2.06 g/day) as compared to the control group (35.28 ± 1.39 g/day, p < 0.001). The CO2/O2 ratio in the treatment (235 ± 14) and control groups (183 ± 9.6) differed significantly (p < 0.001). Overall, PG supplementation (10 g/calf/day) reduced their average methane emission per day and did not adversely affect the growth and development of experimental calves, confirming its useful anti-methanogenic potential.